Black Medic (Medicago lupulina) Emergence and Emergence Predictors within Florida Strawberry Fields. Issue 2 (27th November 2018) - Sharpe, Shaun M.; Boyd, Nathan S.
Abstract: Black medic ( Medicago lupulina L.) infestations are a concern for Florida strawberry [ Fragaria × ananassa (Weston) Duchense ex Rozier (pro sp.) [ chiloensis × virginiana ] producers. Current control techniques rely on hand weeding or clopyralid application. Coordinating POST control measures with emergence timing can reduce crop competition duration and increase control. The objective of this study was to evaluate M. lupulina emergence in response to burial depth and temperature and to model M. lupulina cumulative field emergence under subtropical Florida conditions using growing degree days (GDDs) as a predictor. Two studies were in controlled environments and looked at factors affecting emergence, burial depth, and temperature. A third experiment was a 2-yr emergence study conducted on four commercial strawberry fields in Hillsborough County, FL. Emergence was modeled as a function of accumulated standard and restricted daily GDD accounting, based on M. lupulina dormancy and germination. In Experiment 1, M. lupulina only emerged when seed was deposited on the surface. In Experiment 2, there was three-way interaction among temperature, burial depth, and measurement timing (P<0.0001). Medicago lupulina emerged from as deep as 2 cm at a temperature range between 15 and 25 C. Medicago lupulina field emergence was not consistent between years, although emergence was consistent across four sites in year 1, with 0 emergence in year 2. Dormancy and germination restrictions increased calibration and validation model fit and reduced GDD inflation, making models usable between years. Medicago lupulina primarily emerged during crop establishment, between mid-November and late-December, which corresponds to an ideal timing for control measures before the harvest period.